Expression of SARS-CoV-2 Nucleocapsid (N) Recombinant Protein Using Escherichia coli System - Rizki Aulia Ansari; Uus Saepuloh; Silmi Mariya; Yuliana; Rachmitasari Noviana; Irma Herawati Suparto; Huda Shalahudin Darusman (Bogor Agricultural University, Indonesia, 2023)
One of the main antigen that can be used for serological testing is the nucleocapsid (N) which is the most abundant viral-derived protein in SARS-CoV-2 where this virus can cause COVID19 disease. The aim of this study was to develop the SARS-CoV-2 N recombinant protein using Escherichia coli expression system. A total of 1,089 nucleotides encoding 362 amino acids of SARS-CoV-2 N was cloned to pET-14b vector. The plasmid then expressed in E. coli BL21 (DE3) and induced with 1.0 mM IPTG (Isopropyl-β-d-1-thiogalactopyranoside). The cell was harvested using denaturation lysis buffer due to inclusion body formation of SARS-CoV-2 N protein. Dialysis processed and concentrated using PEG-6000 resulted 0.992 mg/ml protein yield. Analysis of SARS-CoV-2 N recombinant protein using SDS-PAGE technique showed approximately 37.0 kDa specific band target protein. Application of this SARS-CoV-2 N recombinant protein to vaccinated and non-vaccinated antibody serum samples using ELISA technique indicated the significant result of optical density mean at 0.603 and 0.135, respectively. This study revealed that the production of SARS-COV-2 N recombinant protein could be carried out in E. coli expression system under denatured conditions, therefore the methods are more effective in producing the protein as a basic material in immuno-diagnostic assay.